The Role of HR Analytics in Strategic Decision-Making: A Systematic Literature Review - Solihin, Ahmad (Penelitian dan Pengembangan Ilmu, 2024)
In the digital era, HR analytics has become a crucial tool for strategic decision making in organizations. This study aims to explore how HR analytics can support organizational sustainability through data-based decision making. Using a systematic literature review method with the PRISMA approach, this research identifies relevant literature that discusses the integration of HR analytics and sustainability. The research results show that HR analytics can improve organizational performance and support sustainability initiatives by optimizing decision-making processes and facilitating the implementation of environmentally friendly practices. The implications of these findings emphasize the importance of integrating HR analytics in organizational sustainability strategies, while limitations include challenges related to data and privacy. This research recommends further exploration of the integration of HR analytics across various industry sectors to understand the potential and limitations of new analytical tools.